Dampak Destination Management Organization (DMO) terhadap Pengembangan Pariwisata Berkelanjutan di Kabupaten Samosir - Syahrul Syahrul; Abdul Kadir Ritonga; Muhammad Zulfan; Enny Hasriyani (Society, 2024)
This study aimed to evaluate the effectiveness of the Destination Management Organization (DMO) program on tourism development in Samosir Regency. The research employed a causal design, analyzing the relationship between the DMO program and tourism development as the dependent variable. The study’s population included government officials involved in the tourism sector, stakeholders, participants in the DMO program, and tourists. Data analysis was conducted using descriptive methods and the impact analysis approach, complemented by regression analysis performed with SPSS. The findings revealed that the DMO program positively and significantly influenced various aspects of tourism development. Specifically, it contributed to economic growth (21.20%), socio-cultural management (34.20%), environmental sustainability (16.30%), sustainable management (28.70%), and human resource (HR) development (40.40%). While most contributions were categorized as medium, HR development demonstrated a strong positive correlation. Stakeholders actively participated and collaborated in the planning, implementation, and decision-making processes of the DMO program. The program provided significant benefits, including improved stakeholder communication, enhanced service quality, and strengthened tourism promotion in Samosir Regency. Policymakers and stakeholders are encouraged to continue supporting the DMO program to maximize its potential. These findings offer valuable insights into the application of the DMO program, particularly in enhancing competitiveness through effective resource management. The program’s contributions span economic growth, socio-cultural enrichment, environmental sustainability, and HR development, underscoring its comprehensive impact on tourism development.